754 Predictive Clinical-Biological Markers Over the First 3 Years of Nusinersen Treatment in SMA Type 1 Patients (Balneo and PRM Research Journal, 2025)
Background: Werdnig-Hoffmann disease, or type 1 Spinal Muscular Atrophy (SMA), is caused by insufficient SMN protein synthesis due to a genetic defect. Symptoms appear within the first 6 months of life, and without ventilatory support, life expectancy averages 2 years. Objective and Methods: This study aimed to monitor pNF-H neurofilament levels in cerebrospinal fluid (CSF) and serum, serum creatinine, and motor performance during nusinersen treatment to evaluate pNF-H as a predictor of motor outcomes. Biological samples and clinical outcomes from 34 participants were analyzed at 6 months, 1 year, 2 years, and 3 years post-treatment initiation. Results: Most patients showed favorable outcomes, with improved motor assessment scores, increased serum creatinine, and decreased pNF-H levels in CSF and serum. Higher baseline pNF-H in CSF was linked to fewer SMN2 gene copies. The largest pNF-H decrease occurred during the nusinersen loading period, stabilizing at low levels through maintenance. Smaller changes in pNF-H from baseline correlated with better motor outcomes and higher serum creatinine at 2 and 3 years. Conclusions: Nusinersen treatment reduced pNF-H levels, reflecting decreased neuronal degradation, increased serum creatinine due to enhanced muscle activity, and improved motor function. High baseline pNF-H in SMA type 1 may indicate a poorer prognosis for motor improvement.